Staphylococcus aureus Internalized by Skin Keratinocytes Evade Antibiotic Killing - Al Kindi, Arwa; Alkahtani, Abdullah M.; Nalubega, Mayimuna; El-Chami, Cecile; O’Neill, Catherine; Arkwright, Peter D.; Pennock, Joanne L. (Frontiers in Microbiology, 2019)
Staphylococcus aureus causes the majority of skin and soft tissue infections. Half of patients treated for primary skin infections suffer recurrences within 6 months despite appropriate antibiotic sensitivities and infection control measures. We investigated whether S. aureus internalized by human skin keratinocytes are effectively eradicated by standard anti-staphylococcal antibiotics. S. aureus, but not S. epidermidis, were internalized and survive within keratinocytes without inducing cytotoxicity or releasing the IL-33 danger signal. Except for rifampicin, anti-staphylococcal antibiotics in regular clinical use, including flucloxacillin, teicoplanin, clindamycin, and linezolid, did not kill internalized S. aureus, even at 20-fold their standard minimal inhibitory concentration. We conclude that internalization of S. aureus by human skin keratinocytes allows the bacteria to evade killing by most anti-staphylococcal antibiotics. Antimicrobial strategies, including antibiotic combinations better able to penetrate into mammalian cells are required if intracellular S. aureus are to be effectively eradicated and recurrent infections prevented.